Heat exchange processes in volume of fire-tube boiler with non-water heat transfer fluid - A. G. Mikhailov; O. V. Vdovin; E. N. Slobodina (Омский научный вестник)
The article proposes a solution to problems associated with hightemperature heating. The main advantages of high-temperature heat transfer fluid are given. A description is given of the design of a fire-tube boiler and its main components (furnaces and a convective bundle). The process of operation of a fire-tube boiler is considered. The method of thermal calculation of the boiler in accordance with the normative method is described. The characteristic of free and forced convection and criteria describing these processes are given. There is presented criterial equation describing the heat transfer in forced and free convection for a fire-tube boiler. Based on the results of the calculated experiment, the graphs of dependence of dimensionless magnitude at free and forced convection on the heat transfer fluid temperature are constructed.